2017
DOI: 10.4329/wjr.v9.i5.223
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of lumbar lateral recess stenosis in magnetic resonance imaging and clinical symptoms

Abstract: AIMTo assess the correlation of lateral recess stenosis (LRS) of lumbar segments L4/5 and L5/S1 and the Oswestry Disability Index (ODI).METHODSNine hundred and twenty-seven patients with history of low back pain were included in this uncontrolled study. On magnetic resonance images (MRI) the lateral recesses (LR) at lumbar levels L4/5 and L5/S1 were evaluated and each nerve root was classified into a 4-point grading scale (Grade 0-3) as normal, not deviated, deviated or compressed. Patient symptoms and disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…A large number of patients with LBP, despite imaging modalities such as MRI, remains without a specific diagnosis (12). Because almost all lumbar structures are plausible sources of LBP, it may serve as a possible cause (13,14). One of the main causes of LBP is IDD of the lumbar spine (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of patients with LBP, despite imaging modalities such as MRI, remains without a specific diagnosis (12). Because almost all lumbar structures are plausible sources of LBP, it may serve as a possible cause (13,14). One of the main causes of LBP is IDD of the lumbar spine (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the etiology of LSCS is poorly understood, it is clear that LF hypertrophy is known to be one of the main causes contributing to LSCS [ 1 , 2 ]. The experiment explored in this investigation demonstrated that LF thickness in LSCS group was significantly greater than that in the LDH group.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar spinal canal stenosis (LSCS) is one of the most common diseases in the elderly population often with symptoms of low back and leg pain, numbness, and intermittent claudication arising from nerve compression [ 1 ]. Numerous causative factors such as disc protrusion, the bony proliferation of the facet joints, and hypertrophy of the ligamentum flavum (LF) contribute to the development of LSCS.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar spinal stenosis is caused by a combination of anatomical factors; disc prolapse and bulging, facet joint and ligamentum flavum thickening, osteophyte formation and endplate degeneration amongst them [ 1 4 ]. These can occur in isolation or most often as a combination [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lateral recess is bordered by the pedicle laterally, the articular facets posteriorly and the vertebral endplate and disc anteriorly [ 4 ]. As with other types of spinal stenosis changing the pedicle length will influence the dimensions of the affected anatomical area.…”
Section: Introductionmentioning
confidence: 99%